(untitled) (Modern education and development, 2025)
The purpose of this article is to analyse the problems affecting the increase in fuel consumption of mine dump trucks, as well as the efficiency of BelAZ dump trucks. Various methods of determining fuel consumption rates for dump trucks have also been analysed. As a result of the study, data on the operation of dump trucks from the road transport department of the Central Mining Department of Navoi Mining Division of Navoi Mining and Metallurgical Combine were collected, and the factors affecting the consumption of diesel fuel were analysed. As a result of researches the estimation of operational indicators of dump trucks is given, and also the indicators influencing fuel consumption during transportation of rock mass are revealed. In addition, several methods of calculation of fuel consumption are proposed and additional parameters affecting this indicator are determined. As a result of the research, recommendations were developed to improve efficiency by reducing fuel consumption during the operation of dump trucks.